Rule-Based AI System Application on College English Teaching Path Based on Computer-Aided Technology. (23rd March 2022) - Ye, Yanping
Abstract : With the development of the Internet, "Internet Plus" has been widely used in various fields, and the Internet has become a great opportunity to transform CET. People's demand for education, especially higher education, has also increased rapidly. With the attention and investment of the state in recent years, higher education has developed rapidly, accounting for half of China's higher education. However, the increase in the number of students has brought great pressure to CET. How to improve the teaching efficiency of large classes is an urgent problem to be solved. The development of sci and tech, especially computer, has brought us new hope. Computer-assisted instruction has been introduced into CET. However, there are some unreasonable points in the design of computer-aided marking system in China, which is not suitable for CET. It is very important to research and design a computer-aided marking system that can expand CET methods and maximize the integration of English instructional resources. This paper introduces the principle, characteristics, and application fields of AI; analyzes the problems faced by CET; and puts forward a CET path based on computer-aided technology.